Rebranding Kampoeng Lama Tourism Village Through Community Empowerment to Achieve Sustainable Tourism: Rebranding Desa Wisata Kampoeng Lama Melalui Pemberdayaan Masyarakat Untuk Mewujudkan Pariwisata Berkelanjutan - Ramadhan, Ikhlas; Nasution, Dayan Hakam Baihaqi; Tanjung, Alra Dayndivie; Lubis, Muhammad Rizki; Risandy, Muhammad Eman (Jurnal Ilmiah Hospitality Management, 2024)
Kampoeng Lama Village in Pantai Labu District, Deli Serdang Regency, has faced a decline in its image and tourism sustainability following a fire incident at the Paloh Naga Agrotourism site. This incident has negatively impacted the village's attractiveness and overall tourism potential. This study investigates the rebranding of Kampoeng Lama as a sustainable tourism destination through community empowerment. Employing a qualitative descriptive method with a field study approach, data were collected through interviews with key stakeholders, including the heads of the village-owned enterprise (BUMDes) and the tourism community empowerment group (Pokdarwis), along with observations and documentation. The findings reveal critical challenges, such as insufficient promotion, a weakened agrotourism image, and inadequate tourism facilities. To address these issues, a rebranding strategy centered on community empowerment is proposed. Key initiatives include engaging the younger generation in programs like the "Child of Seven Charm" (ASAP) and ecobrick activities to promote environmental awareness, improving tourism infrastructure, creating an integrated tourism map, and optimizing digital platforms such as social media and the Paloh Naga Agrotourism website. These efforts not only restore the village’s image but also increase its visibility and tourist appeal. The urgency of this research lies in the need to revitalize Kampoeng Lama’s tourism potential and address the socio-economic challenges following the decline in its image. The novelty of this study is its focus on a community-driven rebranding approach that integrates environmental awareness and modern marketing strategies. This research contributes a replicable model for restoring and sustaining tourism in rural destinations, ensuring economic growth, environmental preservation, and cultural resilience.